Acute Nontraumatic Muscle Weakness - Jangra, Kiran; Bhagat, Hemant; Takkar, Aastha (Journal of Neuroanaesthesiology and Critical Care, 2019)
Acute nontraumatic weakness (ANTW) is defined as acute onset of weakness in any part of the body. The weakness occurs due to interruption at any point along the motor pathway. The motor pathway originates from upper motor neuron cells in the cerebral cortex and traverses through the brainstem till lower motor neurons in the spinal cord. The axon of a lower motor neuron is known as the peripheral motor nerve that synapses with muscle. ANTW is of varied etiology and presentation that may be immediately life-threatening if respiratory muscles or autonomic nervous system is involved. Involvement of respiratory muscles may be associated with respiratory failure that may require mechanical ventilation. The weakness may be localized to one limb or generalized involving several muscle groups. When bulbar muscles are involved, weakness leads to problem in swallowing and coughing that endangers the patient's airway. Similarly, the course of the disease also varies, and these patients may worsen rapidly. Hence, a comprehensive history, systematic evaluation, and a detailed neurological examination are performed to localize the disorder. There are specific clinical features peculiar to the particular location of the lesion in the body. Hence, it is possible to anatomically localize these lesions based on the clinical features. Initial laboratory tests and appropriate neuroimaging should be obtained as indicated by history and examination. The time-sensitive emergencies should be addressed immediately, as the delay in management may lead to either permanent neurological damage or may worsen the overall outcome in such conditions. The initial management should always include care of airway, breathing, and circulation (ABC). The imaging should be obtained only after initial stabilization of ABC. The definitive treatment should be done as per the etiology.
Keywords: acute weakness; neuromuscular weakness; nontraumatic weakness; respiratory failure